2017
DOI: 10.5455/ajvs.264557
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of Natamycin and Potassium Sorbate on mold growth in Egyptian Fresh soft cheese (Tallaga Cheese)

Abstract: Key words:Natamycin, Potassium sorbate, mold growth, Tallaga cheese One of the most common problems in fresh soft cheese manufacture is fungal growth during storage period. In this respect, this study aimed to control fungal growth in Tallaga cheese by natural preservatives as natamycin (pimaricin) and other allowed substances as potassium sorbate. In this study, we evaluated the effect of different concentrations of natamycin (5, 10 and 20 ppm) and potassium sorbate (0.5 and 1%) and combination of natamycin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Tallaga cheese stored at 4°C for 30 days treated with natamycin (5, 10, and 20 ppm) and potassium sorbate (0.5 and 1%) had very a reduced level of mold growth. 16 Formic acid (98%) and L. plantarum were inoculated at a rate of 3 × 10 10 CFU g −1 and Propionibacterium acidopropionici plus 2.4 L t −1 fresh corn; as a result, all treatment groups had lower pH. This situation was able to reduce the growth of Clostridia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Tallaga cheese stored at 4°C for 30 days treated with natamycin (5, 10, and 20 ppm) and potassium sorbate (0.5 and 1%) had very a reduced level of mold growth. 16 Formic acid (98%) and L. plantarum were inoculated at a rate of 3 × 10 10 CFU g −1 and Propionibacterium acidopropionici plus 2.4 L t −1 fresh corn; as a result, all treatment groups had lower pH. This situation was able to reduce the growth of Clostridia spp.…”
Section: Discussionmentioning
confidence: 99%
“…González -Forte, Amalv & Bertola [45] demonstrated that Natamycin in a cornstarch coating showed an inhibitory effect on the surface of semi-hard cheeses against fungi isolated from dairy factories including Penicillium spp. In a similar study, Küçük et al [52] developed alginate and zein films containing Natamycin (100, 200, 500, 1,000, 2,000, and 4,000 ppm) for kosher cheeses, finding that the inhibitory activities of the coatings against Aspergillus niger and Penicillium camemberti increased as the natamycin concentration increased. Torrijos et al [46] evaluated this compound's invitro antifungal activity against Penicillium sp.…”
Section: Natamycinmentioning
confidence: 97%
“…Research into the application of Natamycin in dairy products is mainly limited to the conservation of cheese, whether in-situ addition or in the production of edible films and packaging [51,52]. In this scenario, the antifungal activity of Natamycin alone (5, 10, and 20 ppm) and combined at 10 ppm with potassium sorbate (1%) was investigated by Ombarak and Shelaby et al [51] in Tallaga cheese stored at 4°C for 30 days, demonstrating inhibitory solid activity against fungi at all concentrations studied, including in synergism with potassium sorbate.…”
Section: Natamycinmentioning
confidence: 99%